Monosynaptic functional connectivity in cerebral cortex during wakefulness and under graded levels of anesthesia - Vizuete, Jeannette A.; Pillay, Siveshigan; Diba, Kamran; Ropella, Kristina M.; Hudetz, Anthony G. (Frontiers in Integrative Neuroscience, 2012)
The balance between excitation and inhibition is considered to be of significant importance for neural computation and cognitive function. Excitatory and inhibitory functional connectivity in intact cortical neuronal networks in wakefulness and graded levels of anesthesia has not been systematically investigated. We compared monosynaptic excitatory and inhibitory spike transmission probabilities using pairwise cross-correlogram analysis. Spikes were measured at 64 sites in the visual cortex of rats with chronically implanted microelectrode arrays during wakefulness and three levels of anesthesia produced by desflurane. Anesthesia decreased the number of active units, the number of functional connections, and the strength of excitatory connections. Connection probability (number of connections per number of active unit pairs) was unaffected until the deepest anesthesia level, at which a significant increase in the excitatory to inhibitory ratio of connection probabilities was observed. The results suggest that the excitatory-inhibitory balance is altered at an anesthetic depth associated with unconsciousness.